2013
DOI: 10.1111/1462-2920.12325
|View full text |Cite
|
Sign up to set email alerts
|

Halomonas sulfidaeris‐dominated microbial community inhabits a 1.8 km‐deep subsurface Cambrian Sandstone reservoir

Abstract: SummaryA low-diversity microbial community, dominated by the γ-proteobacterium Halomonas sulfidaeris, was detected in samples of warm saline formation porewater collected from the Cambrian Mt. Simon Sandstone in the Illinois Basin of the North American Midcontinent (1.8 km/5872 ft burial depth, 50°C, pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for largescale hydrocarbon extraction, as well as subsurface gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 50 publications
0
46
1
Order By: Relevance
“…Genomic DNA for strain Z6 was extracted using the phenol-chloroform extraction method, as described previously (28). The genome was sequenced using the Roche 454 and Illumina HiSeq technologies, with average sequencing coverages of approximately 26ϫ and 140ϫ, respectively.…”
Section: Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic DNA for strain Z6 was extracted using the phenol-chloroform extraction method, as described previously (28). The genome was sequenced using the Roche 454 and Illumina HiSeq technologies, with average sequencing coverages of approximately 26ϫ and 140ϫ, respectively.…”
Section: Mediamentioning
confidence: 99%
“…Our previous work identified indigenous microbial communities within different stratigraphic horizons in the Mt. Simon formation, and using this water, we successfully developed enrichment cultures capable of reducing ferric iron compounds (27,28). In this paper, we describe a bacterium isolated from these enrichments that is capable of reducing a broad suite of iron minerals.…”
mentioning
confidence: 99%
“…As groundwater moves along flow paths from zones of recharge to discharge, its chemistry is altered by a range of geochemical and biogeochemical processes including the weathering and dissolution of rocks and minerals and by the products of microbial oxidation of organic matter and reduction of a range of electron acceptors. In response to increased levels of groundwater salinity, halotolerance has been observed in many bacterial strains isolated from deep terrestrial environments, including oil reservoirs (Tardy-Jacquenod et al, 1998), siltstone formations (Boone et al, 1995), sandstones (Dong et al, 2014), and granitic groundwater . Halophilic growth strategies are encountered in regions characterized by higher salinity concentrations, including ancient deep evaporite deposits (Schubert et al, 2009) and cryopegs in permafrost (Gilichinsky et al, 2003).…”
Section: Physiological Adaptationsmentioning
confidence: 99%
“…The deeply buried Mt. Simon Sandstone contains quartz grains with ubiquitous iron oxide cement coatings and porosity filled with briny water with high concentrations of dissolved ions (Bowen et al, 2010; Locke et al, 2013; Dong et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The studies on the Pennsylvanian Seelyville coal beds (95–100 m depth) on the eastern margin of the Illinois Basin in Indiana (Strapoć et al, 2009) revealed a microbial community dominated by Methanocorpusculum , which may utilize H 2 and CO 2 derived from biodegradation of coal organic matter for methane production (Strapoc et al, 2008). In addition, Dong et al (2014) identified a lowly diversified microbial community inhabiting in the significantly deeper (1.8 km) and more ancient subsurface of the Cambrian-age Mt. Simon Sandstone.…”
Section: Introductionmentioning
confidence: 99%